Lunch eating predicts weight-loss effectiveness in carriers of the common allele at PERILIPIN1: the ONTIME (Obesity, Nutrigenetics, Timing, Mediterranean) study. Issue 4 (14th September 2016) - Garaulet, Marta; Vera, Beatriz; Bonnet-Rubio, Gemma; Gómez-Abellán, Purificación; Lee, Yu-Chi; Ordovás, José M
ABSTRACT: Background: We propose that eating lunch late impairs the mobilization of fat from adipose tissue, particularly in carriers of PERILIPIN1 ( PLIN1 ) variants. Objective: The aim was to test the hypothesis that PLIN1, a circadian lipid-stabilizing protein in the adipocyte, interacts with the timing of food intake to affect weight loss. Design: A total of 1287 overweight and obese subjects [229 men and 1058 women; mean ± SD body mass index (in kg/m 2 ): 31 ± 5] who attended outpatient obesity clinics were enrolled in the ONTIME (Obesity, Nutrigenetics, Timing, Mediterranean) study. Timing of food intake was estimated with a validated questionnaire. Anthropometric variables and PLIN1 genotypes were analyzed, including 6209T>C (rs2289487), 11482G>A (rs894160), 13041A>G (rs2304795), and 14995A>T (rs1052700). The main outcomes were effectiveness of the program and weight-loss progression during 28 wk of treatment. Results: The PLIN1 locus was associated with variability in response to a weight-loss program. Specifically, carrying the minor C allele at the PLIN1 6209T>C was associated with better weight-loss response ( P = 0.035). The probability of being a better responder [percentage of weight loss ≥7.5% (median)] was 33% higher among C than among TT carriers (OR: 1.32; 95% CI: 1.05, 1.67; P = 0.017). We found an interaction of PLIN1 × food timing between the 14995A>T variant and timing of lunch eating for total weight loss ( P = 0.035). Among AA carriers, eating late was associated with less weight loss ( P < 0.001), whereas time of eating did not influence weight loss among TT carriers ( P = 0.326). Conclusions: Variability at the PLIN1 locus is associated with variability in weight loss. Moreover, eating late is related to lower weight-loss effectiveness among carriers of the AA genotype at the PLIN1 14995A>T variant. These results contribute to our ability to implement more precise and successful obesity treatments. The ONTIME study was registered at clinicaltrials.gov as NCT02829619.